(untitled) (International Journal of Innovative Technologies in Economy, 2024)
The decline in the Jakarta Composite Index (JCI) was due to sideways price movements. As a result, stock prices in the Consumer Non-Cyclicals sector also fell. This study aims to help investors focus on the most important elements in investing capital in terms of external and internal assessments in the Consumer Non-Cyclicals sector listed on the Indonesia Stock Exchange. The research population is Consumer Non-Cyclicals sector companies. The purposive sampling method was used in sampling so that out of 126 listed companies, only 35 companies fell into the criteria. Factor analysis was conducted using the SPSS 26 program. The results stated that interest rates, inflation, Return On Equity (ROE) were the dominating factors on stock prices. Meanwhile, Debt to Equity Ratio (DER) does not dominate the stock price in Consumer Non-Cyclicals sector companies for the 2018-2022 period.